2021
DOI: 10.3390/jpm11030164
|View full text |Cite
|
Sign up to set email alerts
|

SOFA Score, Hemodynamics and Body Temperature Allow Early Discrimination between Porcine Peritonitis-Induced Sepsis and Peritonitis-Induced Septic Shock

Abstract: Porcine model of peritonitis-induced sepsis is a well-established clinically relevant model of human disease. Interindividual variability of the response often complicates the interpretation of findings. To better understand the biological basis of the disease variability, the progression of the disease was compared between animals with sepsis and septic shock. Peritonitis was induced by inoculation of autologous feces in fifteen anesthetized, mechanically ventilated and surgically instrumented pigs and contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Unfortunately, to the best of our knowledge, there are no clearly defined large animal model of sepsis phenotypes, in which to explore underlying pathophysiology or to test novel therapeutic targets. Nevertheless, we have recently demonstrated the associations of outcome with clinically relevant phenotypes ( Al-Obeidallah et al, 2021 ). In that study, SOFA score, hemodynamical parameters and body temperature were shown to significantly and early discriminate between sepsis and septic shock in a clinically relevant porcine model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, to the best of our knowledge, there are no clearly defined large animal model of sepsis phenotypes, in which to explore underlying pathophysiology or to test novel therapeutic targets. Nevertheless, we have recently demonstrated the associations of outcome with clinically relevant phenotypes ( Al-Obeidallah et al, 2021 ). In that study, SOFA score, hemodynamical parameters and body temperature were shown to significantly and early discriminate between sepsis and septic shock in a clinically relevant porcine model.…”
Section: Discussionmentioning
confidence: 99%
“…A standard experimental setting may include: a central venous catheter for drug and fluid infusion (inserted through the left jugular vein); a balloon-tipped thermodilution pulmonary artery catheter (placed via the right jugular vein); a femoral arterial catheter for blood pressure recording and blood sampling; a fiberoptic catheter for thermal-dye double-indicator dilution measurements; ultrasound transit time flow probes (e.g., around the portal vein, the common hepatic artery, and the left renal artery); catheters in the portal, renal, and hepatic veins; laser Doppler flowmetry for monitoring ileal mucosal and renal cortex microcirculation; and a cystostomy catheter for urine collection (percutaneous insertion under ultrasound guidance). In case hemofiltration techniques are investigated, a dialysis catheter (e.g., 14-French double-lumen) may be inserted into the right femoral vein and serve for hemofiltration access (Stengl et al, 2010b;Jarkovska et al, 2016;Jarkovska et al, 2018;Al-Obeidallah et al, 2021). Such extensive monitoring allows for a determination of the modified SOFA score according to the Third International Consensus definitions of Frontiers in Physiology frontiersin.org sepsis and septic shock (Singer et al, 2016) with the exclusion of the Glasgow coma scale-based neurologic component due to the use of general anesthesia.…”
Section: General Methodological Aspectsmentioning
confidence: 99%
See 1 more Smart Citation